Concurrent chemoradiation therapy tailored to the older adults with esophageal cancer: state of the art and the future - Song T (Dove Medical Press, 2018)
Tao Song,1 Min Fang,1 Shixiu Wu2 1Department of Radiation Oncology, Zhejiang Provincial People’s Hospital, People’s Hospital of Hangzhou Medical College, Hangzhou 310000, Zhejiang, People’s Republic of China; 2Department of Radiation Oncology, Hangzhou Cancer Hospital, Hangzhou 310000, Zhejiang, People’s Republic of China Purpose: The aim of this study was to review the published literature addressing the question of whether geriatric assessment (GA) should be routinely applied in the treatment of older adults with esophageal cancer (EC) who have received definitive concurrent chemoradiotherapy (dCRT).Materials and methods: A literature search of PubMed, Embase, and Cochrane Library was performed. Studies that contained original data outlining the inclusion and exclusion criteria, treatment compliance rate, and severe toxicity reports were reviewed. Additionally, criteria from ongoing clinical trials in the World Health Organization and National Institutes of Health registries were reviewed to evaluate the utilization of GA-related domains in elderly EC patients who received dCRT.Results: Twenty-nine studies were identified based on the selection criteria: five were single-arm prospective studies, and the other studies were retrospective studies. All studies used chronological age and performance status as basic descriptors for this subpopulation. The comorbidity index and the malnutrition level were mentioned in several studies. However, factors such as “Demographic data and social support,” “Psychology,” “Polypharmacy,” and “Geriatric syndromes” were not described in any of the included studies. Unfortunately, the results were similar for the registered clinical trials. Finally, treatment compliance and toxicity profile were found to be acceptable in selected elderly EC patients.Conclusion: The current experience for older adults with EC receiving dCRT is mainly based on the results of a series of retrospective studies. Ongoing clinical trials should routinely consider GA-related domains to select appropriate treatments for patients in the future. Keywords: older adults, esophageal cancer, chemoradiotherapy, inclusion criteria, toxicity, geriatric assessment